Creative Teaching Strategies to Improve Achievement and Motivation of Higher Education Students in Indonesia - Siti Inayatulloh; Abdul Rivai Saleh Dunggio; Nurjanis Nurjanis; Eka Uliyanti Putri br Bangun (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
Education is a human need that must always develop according to time. The rapid development in the world of education and technology is a benchmark for the quality of increasing the achievement and motivation of higher education students in Indonesia. Therefore, to improve achievement and motivation to learn, the strategy taken is to make changes in terms of learning which is usually too menotonous now no longer, so as a lecturer must be able to create creative teaching strategies so as to improve the achievement and motivation of college students to learn even better, the strategy is to stop changing the way of learning that has been usually too monotonous. Therefore, as a lecturer must be able to develop creative teaching strategies to be able to improve student learning achievement and strengthen motivation, with a more interesting and fun learning strategy so that students are more enthusiastic about learning. The purpose of this study was to determine creative teaching strategies to improve the achievement and motivation of college students in Indonesia. This research method uses quantitative research methods, where the data is obtained from the results of distributing questionnaires online. The results showed that creative teaching strategies were able to improve student achievement and motivation. From this research, it can be concluded that the application of creative teaching strategies which aims to improve student achievement and motivation to learn has proven to be effective. The limitation of this study is that researchers can only conduct research on teaching strategies when there are many more strategies that can increase student creativity and motivation. The researcher hopes that future researchers can conduct research related to teaching strategies to increase student creativity and learning motivation but by using other strategies. This study also recommends that future researchers make this research a reference in conducting research on improving student creativity and motivation through teaching strategies.